2019
DOI: 10.2478/boku-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria for lessivage of profile-differentiated soils of the Precarpathian region (Ukraine)

Abstract: Summary Profile-differentiated soils of the Precarpathian region were formed due to the combined effect of such processes as podzolization, lessivage, gley-eluvium. For the diagnosis of these soils, researchers have used different diagnostic features. The most controversial is the diagnosis of the lessivage process. Based on our own field and analytical studies, it is suggested to use the granulometric composition compared to the contents of the horizon and the silt content in argillanes for the diagnosis of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The formation of Fe-Mn neoplasms in profile-differentiated soils of PreCarpathians occurs due to the alternation of redox conditions, sporadic-pulsation water regime with the participation of specific, nonspecific microflora and glee-eluvial, segregation processes of soil formation. In the laboratory Fe-Mn washing of specific neoplasms on sieves and determination of their content and fractional composition by thermostatic-weight method has been carried out (Pankiv, 2019). Our research found that the gross content of Fe2O3 in the studied soils and especially in Fe-Mn specific tumors is significant, which indicates the important role of iron in the diagnosis of genesis and soil-forming processes (Pankiv et al, 2020a).…”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…The formation of Fe-Mn neoplasms in profile-differentiated soils of PreCarpathians occurs due to the alternation of redox conditions, sporadic-pulsation water regime with the participation of specific, nonspecific microflora and glee-eluvial, segregation processes of soil formation. In the laboratory Fe-Mn washing of specific neoplasms on sieves and determination of their content and fractional composition by thermostatic-weight method has been carried out (Pankiv, 2019). Our research found that the gross content of Fe2O3 in the studied soils and especially in Fe-Mn specific tumors is significant, which indicates the important role of iron in the diagnosis of genesis and soil-forming processes (Pankiv et al, 2020a).…”
Section: Methodsmentioning
confidence: 68%
“…The profile-differentiated soils of the PreCarpathians predominate within the hills (Drohobych, Morshyn, Stevihor-Boloziv), where they occupy the ancient terrace watersheds of the third or fifth floodplain terraces. They were formed on carbonate-free alluvial, deluvial, alluvial-deluvial loamy rocks under conditions of excess moisture, stagnantwashing type of water regime under deciduous and mixed forests on the basis of the combined action of podzolization, silting, siltation and siltation added by segregation (Kanivets et al, 1975;Nikorych et al, 2003;Pankiv et al, 2017;2019). In the process of combined action of soil formation factors and soil-forming processes, sharply differentiated eluvial-illuvial types of profiles with illuminated, silicaenriched upper eluvial part and brown, dark brown (due to accumulation of Fe compounds), heavier with granulometric structure have been formed.…”
Section: Resultsmentioning
confidence: 99%
“…Morphological features have been studied, and soil samples have been taken from all genetic horizons, soil-forming rocks, and soil neoformations (nodules, concretions, argillans, and cutans of iron oxides) in the field conditions within Neocambic Gleyic Retisols (study plot "Hirne", Figure 2) and Stagnic Retisols (study plot "Loyeva", Figure 3). All soil samples were taken in 6-fold repetition with further statistical treatment (Pankiv et al 2019a, Pankiv et al 2019b.…”
Section: Methodsmentioning
confidence: 99%
“…The granulometric composition of soil, argillans, ortsteins, concretions, and nodules have been determined by the method proposed by Kachinskii with the preparation of soil by the pyrophosphate method according to the Dolgov and Lichmanova procedure (Kachinskii 1965). Based on the results of the gross chemical composition of silt, fine soil, and soil (Pankiv et al 2019a, Pankiv et al 2019b neoformations, molar ratios were calculated according to the method proposed by Harrassowitz (profile differentiation indices) (1926), "leaching factor" according to G. Jenny's method (1931), EA coefficients of Fe 2 O 3 , R 2 O 3 , EAt (total eluvial-accumulative coefficient for all oxides) and EAm (eluvial-accumulative coefficient of all oxides except oxide-witness) according to Rode's method (2008). To establish the genesis of nodules, concretions and argillan, the accumulation factor (Cx) has been calculated (Dawson et al 1985).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation